Indian Diaspora in Canada: A Bridge Between Two Democracies - Ahmad Parry, Suheel; Ahmad Bhat, Aaqib (International Journal of Psychosocial Rehabilitation, 2020)
The Indian diaspora in Canada significantly contributes to the improvement of ties between Canada and India. The purpose of this essay is to investigate how the Indian diaspora has improved ties between India and Canada. The article utilizes a dyadic methodology proposed by Mirilovic (2018), who contends that the regime type in both the country of residency and the nation of origin concurrently shapes diaspora politics. Diaspora organizations can be heavily involved in the formalization of foreign policy cooperation in the democracy/democracy dyad. This theory holds that when political activities of the diaspora living in another democracy aim to deepen political relations between the two nations, democracy in the country of origin promotes those efforts. The paper opens with a brief introduction to the topic, noting the many waves of Indian immigration to Canada and the factors that prompted them. Following that, it goes through the demographics, socioeconomic standing, and political outlook of the Indian diaspora in Canada today. The study concludes that the diaspora may serve as a bridge between two democracies, facilitating political collaboration, economic progress, and cultural interchange between their adopted nation and their place of origin.